Pengaruh kualitas produk dan harga terhadap keputusan pembelian di Toserba Borma Cikutra - Mawarnie, Devy; Fahira, Dinda Marsya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The era that is currently underway is driving changes in Indonesia, as well as the increase and development of the business world, which is increasingly rapid. With this comes the rise of the goods and services industry. Retail companies must know what the needs and expectations of consumers are in order to allow them to purchase a product. This study aims to analyze the effect of product quality and price on purchasing decisions. Borma is a department store that is quite large, cheap, and complete because the price is cheap and the goods are quite complete. So the purpose of this research is to know the effect of product quality and price on consumer purchasing decisions at the Borma Cikutra department store. The object of this study is consumers who have made purchases at the Borma Department Store, and the population is unknown. The method used in this study uses multiple linear regression analysis with the SPSS application to process the data. The data used is primary data collected via questionnaires, with samples drawn from 97 Borma department store customers. The results of this study indicate that product quality and price have a significant effect on purchasing decisions.